2009
DOI: 10.1021/op900137j
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Solid Form Screen Approach To Identify a Pharmaceutical Glutaric Acid Cocrystal for Development

Abstract: Pharmaceutical cocrystals could be used to improve the physicochemical properties of active pharmaceutical ingredients. Here, a practical solid form screen approach to identify pharmaceutical cocrystals in the early development stage is proposed. This approach first used a cogrinding screen to identify potential cocrystal former leads that could form cocrystals with the compound of interest, followed by a solvent-based screen to identify, evaluate, and generate the cocrystal candidates. This approach not only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…F7 prepared by slurry method was selected as optimum formulation owing to higher drug release (12.0-93.5%) among all the formulations at pH 6.8. However, the order of in vitro release was: F7 > F8 F6 > F5 > GPZ > The results were supported by various previously reported studies (31,34). Comparative percent drug release from GPZ-GLU (1 : 1) and GPZ-GLU (1 : 2) cocrystals have shown in Figure 8 (A) and (B) respectively.…”
Section: In Vitro Drug Release Studiessupporting
confidence: 85%
“…F7 prepared by slurry method was selected as optimum formulation owing to higher drug release (12.0-93.5%) among all the formulations at pH 6.8. However, the order of in vitro release was: F7 > F8 F6 > F5 > GPZ > The results were supported by various previously reported studies (31,34). Comparative percent drug release from GPZ-GLU (1 : 1) and GPZ-GLU (1 : 2) cocrystals have shown in Figure 8 (A) and (B) respectively.…”
Section: In Vitro Drug Release Studiessupporting
confidence: 85%
“…As part of the screening methodology, the fenamic acids and nicotinamide were suspended or dissolved in an organic solvent in which the solubility of both components was roughly equal, as this is more likely to produce a congruently saturating system (Table S1, Supporting Information). This strategy has been reported to maximize the chance of cocrystal precipitation 25 and indeed, using ethanol as a solvent, was successful in the isolation of the 1:1 cocrystals 1·6 and 2·6. However, the 1:2 cocrystals 3·6 and 4·6 were always observed with residual acid and/or nicotinamide present, even when a wide variety of alternative solvents and 1-10 equivalents of nicotinamide were used.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the rate of cocrystal formation did not depend on the polymorphic form of API used [13]. Recent publications contain some interesting examples of pharmaceutical cocrystals and of practical screening for their design, synthesis, and characterization [10, 14,15].…”
Section: Introductionmentioning
confidence: 99%